The Rebound Effect and Energy Efficiency Policy - Kenneth Gillingham; David Rapson; Gernot Wagner (Fondazione Eni Enrico Mattei (FEEM), 2015)
What do we know about the size of the rebound effect? Should we believe claims that energy efficiency improvements lead to an increase in energy use? This paper clarifies what the rebound effect is, and provides a guide for economists and policymakers interested in its magnitude. We describe how some papers in the literature consider the rebound effect from a costless exogenous increase in energy efficiency, while others examine the effects of a particular energy efficiency policy - a distinction that leads to very different welfare and policy implications. We present the most reliable evidence available quantifying the energy efficiency rebound, and discuss areas where estimation is extraordinarily difficult. Along these lines, we offer a new way of thinking about the macroeconomic rebound effect. Overall, the existing research provides little support for the so-called backfire hypothesis. Still, much remains to be understood, particularly relating to induced innovation and productivity growth.
Keywords: H23; Q38; Q41; 330; Energy Efficiency; Rebound Effect; Take-back Effect; Backfire; Jevons Paradox